The Effect of Capacitance on the Power Factor Value of Parallel RLC Circuits - Hadiningrum, Kunlestiowati; Muldiani, Ratu Fenny; Pratama, Defrianto (Jurnal Internasional Penelitian Teknologi Terapan, 2020)
The power factor of the circuit is determined by the amount of pure resistance (R), self-inductance of the coil (L) and the capacitance of the capacitor (C). In this study, the measurement of the power factor value in a parallel RLC circuit was carried out through experimental testing and simulation with the value of C as the independent variable, while the values of R and L were fixed conditioned quantities. The purpose of this study was to determine the effect of capacitance on a parallel RLC circuit. One of the ways to improve the power factor value in a circuit is to install capacitive compensation using a capacitor. The relation between the power factor value and the capacitance and inductive reactance based on the experimental results and the simulation calculation results in the parallel RLC circuit both shows the same pattern with a relative uncertainty below 8%. The experimental results and simulation results both show that the power factor can be improved by using a right capacitance which is around the capacitance value when there is resonance in the circuit.